Regulation of oxidized base damage repair by chromatin assembly factor 1 subunit A. Issue 2 (27th October 2016) - Yang, Chunying; Sengupta, Shiladitya; Hegde, Pavana M.; Mitra, Joy; Jiang, Shuai; Holey, Brooke; Sarker, Altaf H.; Tsai, Miaw-Sheue; Hegde, Muralidhar L.; Mitra, Sankar
Abstract : Reactive oxygen species (ROS), generated both endogenously and in response to exogenous stress, induce point mutations by mis-replication of oxidized bases and other lesions in the genome. Repair of these lesions via base excision repair (BER) pathway maintains genomic fidelity. Regulation of the BER pathway for mutagenic oxidized bases, initiated by NEIL1 and other DNA glycosylases at the chromatin level remains unexplored. Whether single nucleotide (SN)-BER of a damaged base requires histone deposition or nucleosome remodeling is unknown, unlike nucleosome reassembly which is shown to be required for other DNA repair processes. Here we show that chromatin assembly factor (CAF)-1 subunit A (CHAF1A), the p150 subunit of the histone H3/H4 chaperone, and its partner anti-silencing function protein 1A (ASF1A), which we identified in human NEIL1 immunoprecipitation complex, transiently dissociate from chromatin bound NEIL1 complex in G1 cells after induction of oxidative base damage. CHAF1A inhibits NEIL1 initiated repair in vitro . Subsequent restoration of the chaperone-BER complex in cell, presumably after completion of repair, suggests that histone chaperones sequester the repair complex for oxidized bases in non-replicating chromatin, and allow repair when oxidized bases are induced in the genome.